Roland Barthes’ Analysis of Image Restoration Theory in Digital Era of The Film “Budi Pekerti” - Tri Fitri Nurul Aeni; Riski Apriliani; Sayfiddinkhon Akbarovich Sultonov (Universitas Teknologi Yogyakarta, 2025)
Films, within the field of communication studies, function as media for conveying social, cultural, moral, and political messages through structured systems of signs and narrative forms. This study examines the issue of image restoration in the film Budi Pekerti, which portrays moral conflict and a reputation crisis unfolding within the dynamics of digital communication. This issue is significant because social media has transformed interpersonal interaction and accelerated new mechanisms in the construction of public opinion. Employing a descriptive qualitative approach, this study utilizes textual observation and literature review as data collection techniques. Roland Barthes’s semiotic theory is applied to interpret visual and narrative signs, while William Benoit’s Image Restoration Theory is used to analyze the crisis communication strategies depicted. The analysis proceeds through three stages: identifying denotative, connotative, and mythical meanings. The findings indicate that the five image restoration strategies—denial, evading responsibility, reducing offensiveness, corrective action, and mortification—do not necessarily succeed in fully repairing a damaged reputation. Furthermore, Budi Pekerti illustrates image restoration not only as a communicative tactic but also as a process of moral transformation grounded in empathy and accountability. This study offers a novel contribution by integrating semiotic analysis with crisis communication theory to illuminate the moral dimensions of individual image recovery within Indonesian digital culture. Nevertheless, limitations arise from the absence of empirical audience data and the inherent subjectivity of semiotic interpretation. Future research should incorporate online surveys or audience perception studies to enrich and validate the analytical findings.